Permanencia de prácticas agrícolas tradicionales en el cultivo de Passiflora ligularis “granadilla”, San José de Lupuna Río Nanay. 2023 - Davila Flores, Henry Anderson (2024)
The study highlights the deep-rooted influence of generationally transmitted agricultural traditions in the passion fruit growing community, where the predominant presence of older farmers drives the preservation of traditional practices, although the arrival of young farmers introduces new challenges. Despite family stability and land ownership, the lack of access to training and advice limits the adoption of modern practices. Preference for traditional planting methods and variety in soil preparation reflect cultural influences, while perceptions of pests and diseases highlight the importance of surveillance. Local marketing highlights the economic importance of the crop, with most farmers dedicating half a hectare to the crop and using crop association and strategic location strategies to optimize yield on the plot.